Долання евфемізації в “мові війни” українського медійного та політичного дискурсу - Тараненко, Олена; Taranenko, Olena; Тараненко, Елена (Видавництво Львівської політехніки, 2017)
Кризовий стан українського офіційного дискурсу аналізується в аспекті невизначеності номінацій: збройного конфлікту, його сутності та сторін, статусу окупованих територій України. Загальна ситуація невизнаної війни в її фіксації з боку журналістів розвивається як процес формування евфемізмів та їх подолання: своєрідного викриття “корупції мови” як одного з видів маніпуляції, з одного боку, та виявлення так званих “чужих смислів” у мові війни (за теорією смислової війни Георгія Почепцова), з іншого. Певним орієнтиром “мови війни” є офіційний політичний дискурс. У статті аналізуються промови Президента України за 2016 р., в яких спостерігаємо поступовий відхід від езопової мови щодо оцінки війни з Росією та появу нових меседжів.

Ukrainian media discourse and political rhetoric have been in crisis since 2014, the time of Russian aggression in the east of Ukraine, particularly in terms of nominating both the armed conflict itself, the other party and the root of it. The overall situation regarding the coverage of the unacknowledged war by journalists is developing as a process of creating euphemisms and getting round them afterwards: a certain way of exposing the “language corruption” as a type of manipulation, on the one hand, and revealing the so-called “foreign meanings” in the war language (according to Georgiy Pocheptsov’s theory of war of meanings), on the other hand. Under these challenging circumstances a certain reference point for media discourse is official political discourse. This paper analyzes the speeches of the President of Ukraine, delivered in 2016, which are characterized by his constant retreat from the Aesopian language when assessing the was with Russia and by emerging new messages.

Кризисное состояние украинского официального дискурса анализируется в аспекте неопределенности номинаций: вооруженного конфликта, его сущности и сторон, статуса оккупированных территорий Украины. Общая ситуация непризнанной войны в ее фиксации журналистами развивается как процесс формирования эвфемизмов и их преодоления: своеобразного разоблачения “коррупции языка” как одного из видов манипуляции, с одной стороны, и выявления так называемых “чужих смыслов” в языке войны (по теории смысловой войны Георгия Почепцова), с другой. Определенным ориентиром “языка войны” является официальный политический дискурс. В статье проанализированы речи Президента Украины за 2016 год, в которых наблюдается постепенный отход от эзопова языка в оценке войны с Россией и появление новых месседжей.
Overcoming euphemization in “war language” of Ukrainian media and political discourses
Преодоление эвфемизации в “языке войны” украинского медийного и политического дискурса
Keywords: конфлікт на Сході України; мова війни; евфемізація; війна смислів; conflict in the east of Ukraine; war language; euphemization; war of meanings; конфликт на Востоке Украины; язык войны; эвфемизация; война смыслов; 007; 304; 659.3